Applications Post-Disaster Counseling in Indonesia: Issues and Challenges - Ifdil, Ifdil; Bt Abd Ghani, Faizah (Universitas Muhammadiyah Metro, 2018)
The high frequency of natural disasters occurring in Indonesia has caused specific psychological impacts to the victims like depression, anxiety, stress, trauma-if these are not reduced—and may cause more severe effects like post-traumatic stress disorders (PTSD). Counselors need to be involved in overcoming these problems, and post-disaster counseling is a new focus in the counseling world. To conduct this counseling, counselors need to have unique competencies. Thus, this paper will explain to the counselor basic concepts, knowledge, competences, skills in doing post-natural disaster counseling services, problems, and challenges involved during the post-natural disaster services.